Interaction and Mechanism of Probiotics with Gut Flora and Immune Regulation: A Review - Manyu TANG; Wanqing WANG; Jingwen QIANG; Wei HUA; Shuang WU; Yali LI; Xin ZHEN; Chungeng LI; Yanling CHENG (Shipin gongye ke-ji, 2022)
Probiotics play beneficial roles in improving the host intestinal microecological balance and improving the host health level and health state. It mainly affects the host health by regulating the intestinal microbiota and participating in the immune regulation of various diseases, thus improving the gastrointestinal physiology. Probiotics have considerable potential in the prevention and treatment of gastrointestinal diseases, and a deeper understanding of the mechanisms of their interaction with gut flora and immune regulation are needed. In this paper, the distribution and colonization of probiotics in the intestinal tract, the regulation of probiotics on intestinal flora and intestinal function, and the relationship between probiotics and immune regulation are briefly discussed, in order to provide reference for the future research on the interaction between probiotics and intestinal flora and the clinical application of probiotics.